Heavy Atom Effect Driven Organic Phosphors and Their Luminescent Lanthanide Metal–Organic Frameworks. Issue 7 (11th June 2013) - Balamurugan, Ayyakkalai; Gupta, Arvind Kumar; Boomishankar, Ramamoorthy; Lakshmipathi Reddy, Mundlapudi; Jayakannan, Manickam
Abstract This investigation demonstrates the heavy atom effect (HAE) concept in developing new organic phosphors and engineering the excited‐state energy levels in lanthanide metal ion suprastructures. This was accomplished by coupling two independent energy‐transfer photophysical processes: enhancing the electronic population in the excited triplet state through intersystem crossing (ISC) and transferring the triplet energy to the excited state of the lanthanide ions. A new series of iodo‐substituted carboxylic ligands were synthesised through a tailor‐made approach and complexes with Eu3+ ions to give one‐ and three‐dimensional metal–organic frameworks (MOFs). Single‐crystal structures of the europium complexes revealed the formation of a 1D linear coordination polymer for the monocarboxylate ligand and 3D MOFs for the dicarboxylate ligand. The HAE quenches the S1→S0 transition (self‐fluorescence) in these ligands and promotes S1→T processes for building enhanced excited triplet electronic states. Single‐crystal structures of iodo‐substituted complexes proved that the ligand molecules were held together by strong π stacking. The π stack restricted vibration relaxation and, as a result, these ligands turned into white or yellowish solid‐state organic phosphors. In Eu3+ ion complexes, the solid‐state phosphorescence of the ligands was completely quenched and the triplet excitation energy was channelled into ligand‐to‐metal energy transfer. Thus, the current approach opens up a new strategy for designing luminescent MOFs based on the HAE principle by controlling the excited‐state energy levels.